2013
DOI: 10.1039/c3cp50764e
|View full text |Cite
|
Sign up to set email alerts
|

Hole traps and Cu-related shallow donors in ZnO nanorods revealed by temperature-dependent photoluminescence

Abstract: This work presents positive experimental evidence for the hole traps in ZnO nanorods, which take part in recombination and change the thermal quenching of Cu-related green emission. The evolution of Cu impurity upon annealing, as well as the formation of Cu-related shallow donors with an energy level of ∼0.11 eV are also indicated by temperature-dependent photoluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition, although it is well-known that the presence of lattice defects plays a key role in the physical and chemical properties of ZnO nanostructures, 10,11 many questions still remain due to the lack of conclusive evidence for defects responsible for luminescence properties. 13 In recent years, microwave-assisted chemistry is emerging as a powerful and innovative tool in all areas of synthetic chemistry due to its advantages over other synthetic methods, [14][15][16] such as shortened reaction times, cost-effectiveness, and cleaner reactions compared to conventional routes. 16,17 In particular, Kappe et al 18 reported a critical assessment of the specic role of microwave irradiation in the synthesis of ZnO micro-and nanostructured materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although it is well-known that the presence of lattice defects plays a key role in the physical and chemical properties of ZnO nanostructures, 10,11 many questions still remain due to the lack of conclusive evidence for defects responsible for luminescence properties. 13 In recent years, microwave-assisted chemistry is emerging as a powerful and innovative tool in all areas of synthetic chemistry due to its advantages over other synthetic methods, [14][15][16] such as shortened reaction times, cost-effectiveness, and cleaner reactions compared to conventional routes. 16,17 In particular, Kappe et al 18 reported a critical assessment of the specic role of microwave irradiation in the synthesis of ZnO micro-and nanostructured materials.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of Cu + cations occupy positions in the interstices of the crystal lattice, playing the role of donor impurities with activation energy of 109 meV. The Cu 2+ state is 200 meV lower the bottom energy of the conduction band [22].…”
mentioning
confidence: 99%